FOTOESSAY: FORVILDET: Stillehavsøsters på afveje - Knudsen, Alma Skjold; Jespersen, Amalie Raakilde Bladt; Andersen, Maria Helene; Frandsen, Kristian (Tidsskriftet Antropologi, 2021)
Fotoessay: Forvildet